A Novel Measure of Real-Time Perseverative Thought. (May 2022) - Stade, Elizabeth C.; Cohen, Rivka T.; Loftus, Paddy; Ruscio, Ayelet Meron
Perseverative thinking (PT), or repetitive negative thinking, has historically been measured using global self-report scales. New methods of assessment are needed to advance understanding of this inherently temporal process. We developed an intensive longitudinal method for assessing PT. A mixed sample of 77 individuals ranging widely in trait PT, including persons with PT-related disorders (generalized anxiety disorder, major depression) and persons without psychopathology, used a joystick to provide continuous ratings of thought valence and intensity following exposure to scenarios of differing valence. Joystick responses were robustly predicted by trait PT, clinical status, and stimulus valence. Higher trait perseverators exhibited more extreme joystick values overall, greater stability in values following threatening and ambiguous stimuli, weaker stability in values following positive stimuli, and greater inertia in values following ambiguous stimuli. The joystick method is a promising measure with the potential to shed new light on the dynamics and precipitants of perseverative thinking.